66.7k views
3 votes
Simplify the expression

Simplify the expression-example-1
User SevenDays
by
5.9k points

1 Answer

8 votes

Hi there!

So what we need to do here is this...

Multiply -3/4 with there own parentheses and multiply 2 with it’s own parentthese also.


- (3)/(4) x 5p = 3 (3)/(4) p


-(3)/(4) x 12 = 9

Then do the second parenthese...


2x8=16


2x - (1)/(4) = (1)/(2)p

Add them like this...


( 3 (3)/(4)p + 9 ) + ( 16 -(1)/(2)p )

Simplflied it again.../ since 3 3/4 and 1/2 both have p, add them...


3 (3)/(4) + - (1)/(2)p=3 (1)/(4)p

Add the rest:


3 (1)/(4)p+9+16

Simplify the expression-example-1
User Amarilis
by
6.3k points